2011
DOI: 10.1371/journal.pone.0020579
|View full text |Cite
|
Sign up to set email alerts
|

Broad Surveys of DNA Viral Diversity Obtained through Viral Metagenomics of Mosquitoes

Abstract: Viruses are the most abundant and diverse genetic entities on Earth; however, broad surveys of viral diversity are hindered by the lack of a universal assay for viruses and the inability to sample a sufficient number of individual hosts. This study utilized vector-enabled metagenomics (VEM) to provide a snapshot of the diversity of DNA viruses present in three mosquito samples from San Diego, California. The majority of the sequences were novel, suggesting that the viral community in mosquitoes, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
173
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 62 publications
9
173
1
1
Order By: Relevance
“…Compared with the viral communities found among mosquitoes and bats by approaches similar to those used in this study (13,18,25,107,108), the diversity of viruses found in this agricultural pest insect was much lower. Obviously, host range of the target sampled can play an important role in the diversity of viral sequences detected.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Compared with the viral communities found among mosquitoes and bats by approaches similar to those used in this study (13,18,25,107,108), the diversity of viruses found in this agricultural pest insect was much lower. Obviously, host range of the target sampled can play an important role in the diversity of viral sequences detected.…”
Section: Discussioncontrasting
confidence: 54%
“…Samples were collected in different geographic locations and at different times and probably reflect different ages of D. citri. We also do not know enough about the genetic diversity among the D. citri populations studied here, and it has been demonstrated that the viromes of mosquitoes and bats vary by species, age, space, time, and sample type (13,107).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Surprisingly, gemycircularviruses are exceptionally widespread in nature. The DNA of SsHADV-1-like viruses was detected in a microbial community from the Sargasso Sea (18) and was found in fecal samples of unexplained human diarrhea (20) and in various animal feces (21)(22)(23), insects (such as mosquitoes, dragonflies, and damselflies) (19,(24)(25)(26), and plants (27). SsHADV-1-like viral DNA was found in human brain and serum samples from multiple sclerosis patients (28), in human HIV-positive blood (29), in the cerebrospinal fluids of Sri Lankan patients with unexplained encephalitis (20), in blood samples of experimental rats (30), and in the liver and spleen of a horse with fatal idiopathic hepatopathy (31).…”
mentioning
confidence: 99%
“…Os vírus podem ser encontrados onde quer que a vida se faça presente e é provável que seja a mais abundante e diversificada forma de microrganismo no meio ambiente (Suttle, 2005;Ng et al, 2011a). Os vírus são agentes causadores de doenças em plantas e insetos economicamente importantes, bem como, em insetos-pragas e plantas invasoras .…”
Section: Introdução Geralunclassified